2005
DOI: 10.1080/153765291009976
|View full text |Cite
|
Sign up to set email alerts
|

A Test Procedure for the Determination of (2-Methoxyethoxy)acetic Acid in Urine from Jet Fuel-Exposed Mice

Abstract: A test procedure for the determination of (2-methoxyethoxy)acetic acid (MEAA) was adapted and applied to urine samples from jet fuel (JP-8)-exposed mice using capillary gas chromatography with a mass selective detector (MSD). MEAA is a metabolite and proposed biomarker for exposure to 2-(2-methoxyethoxy)ethanol, a glycol ether component in the formulation of JP-8. The collected urine samples were spiked with deuterated butoxyacetic acid internal standard, and extracted with ethyl acetate, and esterified with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The correlation between I 418 / I 616 and concentrations of MEAA can be rationalized by the equation I 418 / I 616 = 0.9818 C MEAA + 0.20587 ( R 2 = 0.99). On the basis of the standard deviation for 20 repeated fluorescence measurements of blank solutions ( S b ) and the slope of the fitting line ( k ), the limit of detection (LOD) of Eu 3+ @ Cd-MOF toward MEAA is calculated to be 8.5 μg mL –1 using the formula LOD = 3 S b / k , , which is close to that of some reported determination methods …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The correlation between I 418 / I 616 and concentrations of MEAA can be rationalized by the equation I 418 / I 616 = 0.9818 C MEAA + 0.20587 ( R 2 = 0.99). On the basis of the standard deviation for 20 repeated fluorescence measurements of blank solutions ( S b ) and the slope of the fitting line ( k ), the limit of detection (LOD) of Eu 3+ @ Cd-MOF toward MEAA is calculated to be 8.5 μg mL –1 using the formula LOD = 3 S b / k , , which is close to that of some reported determination methods …”
Section: Resultssupporting
confidence: 80%
“…Early in 2003, B’Hymer et al realized the quantitative determination of MEAA in human urine with gas chromatography-mass spectrometry (GC-MS) systems . To date, gas chromatography (GC) methods have been developed into the main techniques applied to assess the biomarker MEAA. ,, Nevertheless, these detection methods require cumbersome pretreatment operations and relatively sophisticated instruments. Therefore, the development of a highly sensitive, easy-to-operate, and low-cost method for the rapid and accurate determination of MEAA in human urine and serum is becoming increasingly urgent.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the wicking properties of cotton tend to enhance dermal exposure and adsorption of JP-8; this can lead to erythema and irritation of the skin. JP-8 has been demonstrated to have significant dermal uptake in mice (B'Hymer, et al 2005b) and represents a significant health concern. Therefore, personal protective equipment changes, especially in clothing materials and the type of clothing used, could easily be evaluated in future studies by measuring urinary MEAA.…”
Section: Discussionmentioning
confidence: 98%
“…Statistically, the MEAA means of the high, moderate, and low (control) exposure categories differ significantly for both creatinine-adjusted and nonadjusted concentration levels, unlike BMA and PMA. The gas chromatographic method (B'Hymer et al 2003;2005a) used in this study appears to have adequate MEAA sensitivity for its use as a biomarker of exposure. MEAA, therefore, is clearly associated with JP-8 exposure work-groups and has the potential for good predictive value, a desirable characteristic of a well-chosen biomarker of occupational exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the low frequency of use of the parent compound, the MEAA metabolite has not been detected in the general population and should not appear in any significant quantity in a control population. MEAA has been studied for use as a biomarker previously in both humans (B'Hymer et al 2012) and animals (B'Hymer et al 2005a;Richards et al 1993). It has also been demonstrated that MEAA is the urinary metabolite best suited for use as a short-term biomarker for exposure to 2-(2-methoxyethoxy)ethanol (Richards et al 1993).…”
Section: Hhs Public Accessmentioning
confidence: 99%